2015
DOI: 10.3109/13880209.2015.1037003
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and biological activities of essential oil ofBeilschmiedia pulverulenta

Abstract: Context: The ethnopharmacological study of Beilschmiedia indicates that several species are used for the treatment of various ailments. Objective: This is the first study of the chemical composition of Beilschmiedia pulverulenta Kosterm (Lauraceae) essential oil and its antioxidant, antimicrobial, antityrosinase, antiinflammatory, and anticholinesterase activities. Materials and methods: The antioxidant activities were evaluated by b-carotene, 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging, ferric-red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined by broth microdilution method using 96‐well microplates described by Salleh et al . () with slight modifications. The inocula of the microbial strains were prepared from 24 h broth cultures and suspensions were adjusted to 0.5 McFarland standard turbidity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined by broth microdilution method using 96‐well microplates described by Salleh et al . () with slight modifications. The inocula of the microbial strains were prepared from 24 h broth cultures and suspensions were adjusted to 0.5 McFarland standard turbidity.…”
Section: Methodsmentioning
confidence: 99%
“…Nine microorganisms; three Gram-positive bacteria; Bacillus subtilis (ATCC6633), Staphylococcus aureus (ATCC29737), Enterococcus faecalis (ATCC19433), three Gram-negative bacteria; Pseudomonas aeruginosa (ATCC9027), Escherichia coli (ATCC10536), Klebsiella pneumonia (ATCC13883), and three fungal/yeast Aspergilus niger (ATCC16888), Candida glabrata (ATC C2001) and Saccharomyces cerevisiae (ATCC7754) were used. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined by broth microdilution method using 96-well microplates described by Salleh et al (2015b) with slight modifications. The inocula of the microbial strains were prepared from 24 h broth cultures and suspensions were adjusted to 0.5 McFarland standard turbidity.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The essential oil capacity of O. basilicum to scavenge free radicals was evaluated by the ability to capture the radical of DPPH. 8 First, a stock solution (1000 μg/mL) was prepared in methanol and then a series of a diluted sample in methanol were prepared to yield a sample (200 μL, 15.63-1000 μg/mL) in disposable cuvettes. Then DPPH (3800 μL, 1000 μg/mL) in methanol was added to each cuvette.…”
Section: Measurement Of Antioxidant Activity Using Dpphmentioning
confidence: 99%
“…Percentage of major constituents (%) 8 Turkey Linalool (45.7), Eugenol (13.4), methyl eugenol ( Many studies have reported the effect of cultivation site on the components of the essential oil of O. basilicum. For example, methyl chavicol presents as the highest main content in the Nigerian O. basilicum (60.30%).…”
Section: Locationmentioning
confidence: 99%